Can Endocan Predict Late-Onset Neonatal Sepsis? - Buyuktiryaki, Mehmet; Tayman, Cuneyt; Okur, Nilufer; Serkant, Utku; Cakir, Ufuk; Halil, Halit; Oncel, Mehmet Yekta; Oguz, Serife Suna (Journal of Pediatric Infectious Diseases, 2019)
Objective Endocan, a proteoglycan secreted by endothelial cells, plays a role in the pathogenesis of sepsis. Endocan is an effective diagnostic and prognostic biomarker of sepsis in adult patients. We evaluate the utility of endocan as a new biomarker in the recognition of late-onset neonatal sepsis (LOS) in preterm infants.Methods This study included preterm infants at gestational age ≤ 32 weeks diagnosed with LOS. Sepsis was diagnosed in the presence of three or more clinical findings plus significant elevation of C-reactive protein (CRP) or interleukin 6 (IL-6) levels. Blood samples were obtained to determine leukocyte count, CRP, IL-6, and endocan levels immediately after the sepsis diagnosis and on the 3rd and 7th day after diagnosis.Results A total of 102 preterm infants, 52 with LOS (21 proven, 31 suspected sepsis) and 50 controls, were included in the study. Mean leukocyte count, serum CRP, IL-6, and endocan levels were significantly higher in the LOS group compared with healthy controls (p < 0.001) at enrolment. Serial measurements showed no significant difference in CRP and IL-6 levels between the proven and suspected sepsis groups, while endocan levels were significantly higher at enrolment and on day 7 in the proven sepsis group (p = 0.003 and p = 0.01, respectively). The endocan levels of preterm infants who died were significantly higher at all time points (p < 0.001, p = 0.001, and p = 0.004, respectively).Conclusion Endocan is an effective, reliable, and promising new biomarker for detecting LOS in preterm infants.
Keywords: endocan; CRP; IL-6; preterm infants; late-onset neonatal sepsis